2008
DOI: 10.1364/oe.16.011405
|View full text |Cite
|
Sign up to set email alerts
|

Fast all-optical flip-flop based on a single distributed feedback laser diode

Abstract: Since there is an increasing demand for fast networks and switches, the electronic data processing imposes a severe bottleneck and all-optical processing techniques will be required in the future. All-optical flip-flops are one of the key components because they can act as temporary memory elements. Several designs have already been demonstrated but they are often relatively slow or complex to fabricate. We demonstrate experimentally fast flip-flop operation in a single DFB laser diode which is one of the stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…Recently, we demonstrated that a single DFB laser diode can act as a broadband AOFF under the injection of continuouswave light [6]. By using an array of DFB lasers where each laser has a different lasing wavelength matched to the WDM grid, one can switch a laser in the array ON and OFF simply by injecting an optical pulse.…”
Section: Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that a single DFB laser diode can act as a broadband AOFF under the injection of continuouswave light [6]. By using an array of DFB lasers where each laser has a different lasing wavelength matched to the WDM grid, one can switch a laser in the array ON and OFF simply by injecting an optical pulse.…”
Section: Conceptmentioning
confidence: 99%
“…Recently, we demonstrated that a single antireflection-coated distributed-feedback (DFB) laser with a -shift operates as a fast AOFF under the injection of continuous-wave light [5], [6]. DFB lasers are already widely used in today's telecommunication industry and the added functionality as optical memory element offers, therefore, an economically viable way to achieve all-optical packet switching.…”
Section: Introductionmentioning
confidence: 99%
“…Digital Object Identifier 10.1109/JQE.2014.2378376 The AOFF based on an anti-reflection-coated (AR-coated) λ/4-shifted distributed feedback (DFB) laser diode, which has been already experimentally demonstrated [14], [15], has the main advantage that it can operate over a broad wavelength range for the set and reset pulses and that it is based on mature device technology. It requires externally injected light, but there are no hard wavelength requirements for the external beam.…”
Section: Introductionmentioning
confidence: 99%
“…By injecting a short but strong pulse at the same side of the device as the CW beam, one can switch from a lasing state (with low gain and uniform carrier density) to a non-lasing one (with high gain and non-uniform carrier density). The uniform carrier distribution can then be restored by injecting a light pulse at the other side of the device [15]. The influence of the bias current and normalized coupling coefficient (κL) on the bistability has been investigated before [14].…”
Section: Introductionmentioning
confidence: 99%
“…Significant research has been done for AOFF operation based on various semiconductor optical devices such as Fabry-Perot Laser diodes (FP LDs), distributed feedback (DFB) LDs, semiconductor optical amplifier (SOA) and microdisk lasers [1][2][3][4][5][6][7][8][9][10][11]. An ultimate goal of such devices is demonstration of low power consumption, high-speed operation, and high-density integration for practical system applications.…”
Section: Introductionmentioning
confidence: 99%